Productive characteristics of maize hybrids at different cutting heights for silage and organic matter and mineral rates in post-harvest residues - doi: 10.4025/actascianimsci.v35i2.16642 - Clóves Cabreira Jobim; Fabio Cortez Leite de Oliveira; Valter Harrys Bumbieris Junior; Michele Simili da Silva (Acta Scientiarum. Animal Sciences, 2012)
Current trial evaluated yield, organic matter and mineral composition of the residual harvest of five maize hybrids at three cutting heights (15, 35 and 55 cm). The experimental design consisted of a randomized block split plot with three replications. Concentrations of N, P, K, Ca, MS, MM and MO in the samples were evaluated. No difference among hybrids occurred in stem diameter (22.4 mm), ear production (8.0 ton DM ha-1), grain harvest index (37.3%) and total forage yield (15.0 ton DM ha-1). Hybrid effect occurred for variables of mineral composition of harvest residues. With the exception of calcium, a rise in cutting height from 15 to 55 cm failed to increase the concentration of minerals in the residue. The amount of organic matter and mineral residues that remained in the field increased in proportion to crop height.